Study of Methane Producing Bacteria from Rice Paddy Field Soil and Rice Roots by Fluorescent In Situ Hybridization Technique - Jirasak Kongkiattikajorn; Winai Keawsawat; Somkiatti Tachakanchanarag (Agriculture and Natural Resources, 2005)
One of the sources of gas methane in the atmosphere causing the world warming comes from paddy fields which are the habitats of methane producing bacteria. Root zone soil and rice roots cv. Suphanburi 90 and Homsuphanburi provided by Rice Research Center Pathum Thani were studied for characterization of methane producing bacteria. The samples were inoculated in basal broth medium in serum vials under anaerobic condition and incubated at 37°C for 40 days. Methane in the vials was determined by gas chromatography. The results showed the methane producing bacteria from the soil of the paddy field of the rice cv. Suphanburi 90 and Homsuphanburi could produce methane at maximum rate of 0.7 and 0.6 ml/g/day at 17 days of incubation, respectively. The microorganisms from the rice root cv. Suphanburi 90 and Homsuphanburi could produce methane at maximum rate of 0.6 and 0.5 ml/g/day at 22 days of incubation, respectively. On determination the type of methane producing bacteria by FISH technique, it was found that the microbacteria from rice root was characterized to be Methanosarcina sp. while the microbacteria from the soil was characterized to be Methanosatae sp. The number of the methanogenic bacteria from the soil and rice root of the rice cv. Suphanburi 90 determined by MPN method was found to be 3.49 × 107 and 2.01 × 103 cell/g, respectively, while the number of the methanogenic bacteria from the soil and rice root of the rice cv. Homsuphanburi was 3.75 × 105 and 5.22 × 103 cell/g, respectively.